Resúmenes bibliograficos: volumen 46, número 1 - De Biasi, Aicia E. (1970)
Incluye: - Procenko, A. E. A natural classification of phytopathogenic viruses. Phytopath - Graham-Rack, Barry and Raymond Binsted, Hygiene in food manufacturing and handling